Legal Protection of Land Use in the Context of Opening and Development of Agricultural Land for Public Interests - Akiruddin Ahmad (PT Inovasi Pratama Internasional, 2022)
Land as a source of life and one of the important factors of production, besides being able to guarantee the availability of space to build infrastructure and facilities for development needs in accordance with the priorities that have been set, it is also necessary to maintain its fertility and sustainability in order to create a comfortable living environment. The pattern of land use in supporting development will experience a shift in accordance with developments in each development sector. Policies in the land sector are aimed at achieving three main things that complement each other, namely efficiency and economic growth, social justice, environmental conservation and sustainable land use patterns. Government has given legal protection to agricultural land by issuing several regulations such as Law Number 41 of 2009 concerning the Protection of Sustainable Food Agricultural Land. This rule emphasizes that sustainable food agricultural land must be protected and cannot be converted unless it is in the public interest.